Comparison of Environmental Laws in the Management of Plastic Waste in Indonesia and Malaysia - Faiz Rahmanto; Dimas Abi Galoga Dasopang (Journal Of Legal Studies Judex Praetor, 2025)
Plastic waste has become a pressing global environmental issue due to its non-biodegradable nature and long-term ecological impacts on terrestrial and marine ecosystems. Indonesia and Malaysia, as two countries with high plastic waste production, face similar challenges in developing effective environmental regulatory frameworks. This study aims to analyze the environmental legal regulations governing plastic waste management in Indonesia and Malaysia and to identify the substantive similarities and differences between the two systems. This research employs a normative legal method with a descriptive analytical approach, using statutory, comparative, and conceptual approaches. Data were obtained through library research involving legislation, academic literature, and legal materials relevant to plastic waste governance. The findings show that both Indonesia and Malaysia adopt sustainability principles, extended producer responsibility, and national roadmaps to reduce single-use plastics. However, significant differences exist in regulatory structures and institutional arrangements. Indonesia’s regulatory framework remains sectoral and does not explicitly regulate systematic stages of plastic waste management, whereas Malaysia has a more structured system comprising six stages supported by a dedicated agency (SWCorp). Further differences include the effectiveness of implementation and the degree of authority given to local governments in formulating plastic reduction policies. This study highlights the need for regulatory harmonization and institutional strengthening to enhance the effectiveness of sustainable plastic waste management.